Differential rates of return and racial wealth inequality - Luke Petach; Daniele Tavani (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2020)
Using data on household balance sheets from the Survey of Consumer Finances and data on macroeconomic rates of return from Jordà et al. (2019) we construct two alternate series for household rates of return by race from 1989 to 2016. Our estimates suggest a persistent racial gap in the rate of return on assets between 1 and 6 percentage points. The gap in returns remains even after conditioning on demographic factors, labor market factors, credit history, portfolio composition, household attitudes toward savings, financial literacy, and inheritance - suggestive of a role for discrimination. Oaxaca-Blinder decompositions indicate that differential rates of return may explain up to 50% of the racial wealth gap. Finally, our data on differential rates of return allow us to effectively rule out explanations for the racial wealth gap based on myopia or excessive time preference. Given observed series for consumption and rates of return, a standard lifecyle model requires non-White households to discount the future less than White households in order to match the data.
Keywords: Z13; D31; G51; 330; Rates of Return; Racial Wealth Inequality